ANALISIS TERJEMAHAN TINDAK TUTUR ILOKUSI KALIMAT TANYA PADA KOMIK LAND OF BLACK GOLD DAN NEGERI EMAS HITAM - Setya Nurvrita, Ardya (Widya Warta, 2017)
The aim of this reseach is to describe questions illocutionary speech act in comic Land of Black Gold and Negeri Emas Hitam. This reseach is decriptive, qualitative research. The result of the analysis are: there are three kinds of questions; Yes-no question, Wh question, and Alternative question. The data applied 10 illocutionary functions; asking, confirming, offering, suggesting, commanding, forbiding, convinceing, reminding, blaming, ensuring. The applying of translation technique of question illocutionary translated by using a single variant technique; Established Equivalent, Literal Translation, Reduction, Linguistics Compression, Modulation, Amplification, Particularisation, Linguistic Amplification, Variation and Couplet variant: Established Equivalent+Reduction,Â  Variation+Literal Translation, Reduction+Amplification, Linguistic Compression+Reduction, Established Equivalent +Variation. Concerning with translation quality can be concluded that the translation has a good quality. Image, text, and narration are ones of the comicâ€™s rules that are interconnected.